Mathematical communication profile of female student who is mathematics teacher candidate in implementing teaching practice program - Hidayah Ansori; I Ketut Budayasa; St Suwarsono (Math Didactic: Jurnal Pendidikan Matematika, 2019)
Students who are mathematics teacher candidates have different mathematical communication skills. They carry out mathematics learning when doing teaching practice. Their mathematical communication skills greatly influence the communication that is implemented into mathematics learning in the classroom. This study aims to describe the mathematical communication profile of female students who are mathematics teacher candidates. The participant of this study was a female teacher candidate who was carrying out teaching practice (PPL) at the training school. Data collection was done by recording the implementation of learning, which was presented through learning video transcripts and analyzed by data reduction, data displaying, and interpretation-verification. The results of this study are prospective female teachers always ask students to repeat their answers, to ensure the answers mentioned. This has resulted in the fact that female mathematics teacher candidates are not strict in making decisions, seem rambling in making decisions. The nonverbal communication of female teacher candidates is a clear voice heard throughout the class; ways/gestures, movements of appearance and facial expressions show calmness and smile to students, so learning flows smoothly.